KONTRIBUSI RETRIBUSI KEBERSIHAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) PADA DI NAS KEB ERSIHAN KABUPATEN LEBAK - Marshal Smith; Maratul Karimah (Universitas La Tansa Mashiro, 2017)
Efforts to increase Regional Original Revenue (PAD) can be done by inclusion in each PAD income, one of which is the contribution of Cleanliness Retribution. This income from cleaning fees can have an influence on the level of Regional Original Income (PAD). The objectives of this study were (1) to find out the receipt of cleaning fees from Lebak residents at the Lebak Regency Sanitation Service (2) to determine the realization of local revenue at the lebak district sanitation department (3) to determine the effect of the contribution of cleaning fees on the LAD district PAD.In this study there was no population and sample because this study was a typical study activity. The results of his research on the average of PAD is 18565859800.00 while the average of the Cleaning Levy itself is 22536583.33 and Std. Deviation which shows the standard deviation from PAD is 8267432213,223 while Std. Hygiene Deviation Retribution 5719415,824 and the amount of PAD data there are 60 Results of simple linear regression Constant (a) of -341432748,355, while the value of Levy (b / regression coefficient) is 838,960, so the regression equation can be written Y = -341432748, 355 + 838,960. And based on the value of t, it is known that the value of tcount is 5.428> t table 2.002, R Square is 33.7%, the remaining 66.3% is measured by other variables. Decision making in the Simple Regression Test, where based on the significant value of the Coefficient is 0.000 <0.05, so it can be concluded that the Retribution variable (X) affects the PAD Variable (Y).